Hitler's War on Russia : The Story of the German Defeat in the East - Carell, Paul; Translated by Osers, Ewald (GHQ, Rawalpindi Army Book Club, 1979)
The classic! This new edition of Paul Carrell's eastern front study picks up where Hitler Moves East left off. Beginning with the battle of Kursk in July 1943, Carell traverses the vast expanse of the Russian War, from the siege of Leningrad and the fierce battles of the norther front, to the fourth battle of Kharkov, and the evacuation of the Crimea, a withdrawal forbidden by Hitler. The book ends in June of 1944 when the Soviet Armies reach the East Prussian frontier. Hundreds of photographs, situation and campaign maps, complete index, and comprehensive bibliography, add to this impressive account. This edition includes a new preface by the author.
Include Illustrations, Appendix, Bibliography and Index.
Translated from the German by Ewald Osers.
Keywords: Hitler's War -- War on Russia -- Paul Carell -- Carell, Paul -- World War (1939-1945) -- Military campaigns -- Eastern Front (World War (1939-1945))